ANALISIS PERUBAHAN CADANGAN HARA PADA BERBAGAI PENGGUNAAN LAHAN DAN KELERENGAN DI DAS MIKRO KALI KUNGKUK, KOTA BATU - Refki Aulia Wiwaha; Syahrul Kurniawan (Jurnal Tanah dan Sumberdaya Lahan, 2021)
The Kali Kungkuk micro watershed which is located in the upper area of Brantas watershed, had Â experienced forest conversion to horticulture during the last fourth decades. Since the physiographic of Kali Kungkuk micro watershed is hilly, forest conversion to horticulture may result in soil nutrient stock changes. The research aimed to analyze soil nutrient stock from forest to horticulture land uses (i.e. apple orchard and vegetables) in the Kali Kungkuk micro watershed. The field research was conducted on three different land uses (i.e. vegetable land (PK), apple orchard (PA), and forest (PH)) and four land slope classes (i.e. slope 0-8% (K1), 8-15% (K2), 15-25% (K3), and > 25% (K4)), with three, replicates plots of each. Soil samples were collected at three different depths (0-10, 10-30, and 30- 50 cm) from each plot. The parameters measured included soil texture, bulk density, standing litter mass, canopy cover, basal area, soil organic carbon and total Â nitrogen. Data analysis was conducted with Linear Mixed Effect Models with a level of 5% and a further analysis of LSD test level of 5% as well as a correlation test between observational parameters. The results showed that differences in land use and slope affected to significant differences in the content of soil organic C and total N. In general, forests had higher soil C and N stocks as compared to other land uses (i.e. apple orchard and vegetables). Furthermore, soil organic C and total N was higher in the low slopes (i.e. 0-8%) and (8-15%) as compared to the high slopes (i.e. 15-25%) and (> 25%). The study found a positive correlation between soil nutrient stocks (i.e. C and N) and clay content. In contrast, soil C and N stock was negatively correlated with soil bulk density. Soil fertility degradation that occurs in the Kali Kungkuk micro watershed (i.e. apple orchard and vegetables) requires serious attention in soil management in order to ensure the sustainability of apple and vegetable production.